The changing roles of MUI’s fatwas in the realization of Indonesian government’s new normal policy - Tarantang, Jefry; Hasan, Ahmadi (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study examines the actualization of the role of the Indonesian Ulema Council fatwa, which is a manifestation of social morality, including in guarding the realization of the new normal times during the COVID-19 pandemic, it is not enough just to fulfill or just provide support in the form of spiritual and moral. But it is also a responsibility to the people, especially to make joint efforts to prevent the spread of the Covid-19 virus outbreak. This study is a retrospective study that focuses on discussing the fatwa of the Indonesian Ulema Council and the actualization of its role in social change. Of course, the fatwa of the Indonesian Ulema Council is more responsive than other legal products, starting from the period before the Covid-19 pandemic, during the time facing the Covid-19 pandemic, even in guarding the realization of the new normal. The presence of the fatwa of the Indonesian Ulema Council is a guarantee of legal certainty (religious insurance approach) in providing peace for Muslims in Indonesia, both in carrying out worship, vaccinations, and the field of muamalah during the Covid-19 pandemic, but will return to normal worship. while the field of muamalah follows the dynamics of changing times and needs. Of course, the domain of legal certainty from the Indonesian Ulema Council in the form of legal products in the form of fatwas provides justification and legitimacy for government policies during the COVID-19 pandemic in accordance with the objectives of Islamic law (maqashid sharia) and the benefit of society.